An Extended Quarterly Projection Model : Credit Cycle, Macrofinancial Linkages and Macroprudential Measures: The Case of the Philippines - Karam, Philippe (IMF Working Papers; Working Paper ;, 2021)
We extend a modern practical Quarterly Projection Model to study credit cycle dynamics and risks, focusing on macrofinancial linkages and the role of macroprudential policy in achieving economic and financial stability. We tailor the model to the Philippines and evaluate the model's properties along several dimensions. The model produces plausible dynamics and sensible forecasts. This along with its simplicity makes it useful for policy analysis. In particular, it should help policymakers understand the quantitative implications of responding to changes in domestic financial conditions, along with other shocks, through the joint use of macroprudential and monetary policies.